A Recommendation on Themes for Teaching Urban Public Finance Course - Jhonny Patta (The Institute for Research and Community Services, Institut Teknologi Bandung, 2007)
This article recommends the themes that ï¬t to be the syllabus of teaching urban public ï¬nance. They are derived from the standard literatures in pubiic finance. Five themes are identifird namely microeconomic rational of urban public ï¬nance, public choice of ï¬scal policy, fiscal federalism, urban policy revenue resources, and budgeting and financial analysis. While ï¬nancing development is a sin qua non theme for developing countries, adjustment will be needed to fit the context of the countries.Keywords: urban, public finance, classic readings